Neighbor selection algorithm in cloud-assistant P2P-VoD system - Xin CONG; Kai SHUANG; Sen SU; Fang-chun YANG; Xin SUN (Tongxin xuebao)
A neighbor selection algorithm was proposed which was composed of sub-algorithms of peer selection and chunk selection.The peer selection algorithm assured that the peers could find the neighbors providing the video data at a high probability.The chunk selection algorithm helped peers choose the methods of downloading data,from which the data chunks could be used at a high availability.The experiment demonstrates that the algorithm can further decrease the server bandwidth costs and the refusal rate of peers' requisition,and improve the download rate of peers.